Modulation by nitric oxide and prostaglandin of the renal vascular response to angiotensin II (3-8). - Yoshida, M. (1996)
1. The aim of this study was to investigate the renal vascular response to angiotensin II (3-8) (AIV). The effect of the nitric oxide synthase inhibitor, NG-nitro-L-arginine methyl ester (L-NAME) or the cyclooxygenase inhibitor, indomethacin on the AIV-induced response was examined in anaesthetized spontaneously hypertensive rats (SHR) and normotensive Wistar-Kyoto rats (WKY). 2. Intrarenal infusion of AIV produced a biphasic vasoconstrictor response. The vasoconstriction developed rapidly to reach a maximum followed by a partial recovery to a sustained lesser level of vasoconstriction. The initial maximum response was enhanced by L-NAME but not affected by indomethacin treatment. The simultaneous administration of L-NAME and indomethacin prevented the partial recovery resulting in a greater sustained level of constriction. 3. A stable vasoconstriction of relatively constant magnitude was observed with angiotensin II (AII) infusion. The AII vasoconstriction was enhanced by L-NAME but not changed by indomethacin. The combination of these inhibitors further enhanced the AII-induced vasoconstriction in WKY, but not in SHR. 4. Pretreatment with the AII receptor antagonist, losartan, inhibited the vasoconstriction induced by AIV and AII. 5. These results suggest that nitric oxide and prostaglandins may modulate the renal vascular response to AIV.